The sixth and earlier seventh centuries: preconditions of the rise of the emporia - Bavuso, I (2017)
This thesis assesses the sixth-/early seventh-century socio-economic roots of the eighth-century transmarine system connecting England and the Continent through major coastal trading sites (emporia). Part 1 discusses socio-economic developments in the coastal areas of Kent, Sussex, Hampshire and the Isle of Wight, and the Pas-de-Calais, through a close investigation of fifth- to early seventh-century archaeological evidence. The inclusion of later written sources has been fundamental to recognise that the two shores of the Channel were connected in a more complex network than previously assumed, beyond the major emporia. These areas are then considered comparatively: after challenging substantivist approaches that assume an overwhelming importance of gift-exchange in sixth-century England, Part 2 stresses the role of transmarine traffic and exploitation of natural resources in the socio-economic development of coastal areas. The examination of sixth-century written sources has also proved rewarding to reconsider the sixth-century political relationships between Franks and Anglo-Saxons. The role of kings, churches and laymen in the later transmarine network (seventh/eighth centuries) is then discussed by including the Thames Valley, the estuaries of the rivers Seine and Loire, and the Rhine Delta, examined through the written sources. One crucial question is the role of political actors in the development of a cross-Channel system of exchange. In this regard, scholars have mainly focused on the period when this system was already in place, pointing to a pivotal role of kings and political institutions for its establishment, or to the later appropriation by elites of a coastal area already integrated in the maritime network, but detached from political power. This thesis argues that a close link existed between elites and coastal areas before the emporia; thus, although kings were not the driving stimulus for the establishment of trading sites, the transmarine traffic fostered the socio-economic development of the coastal communities.